Cryopreserved, Thin, Laser-Etched Osteochondral Allograft maintains the functional components of articular cartilage after 2 years of storage - Carolyn B. Rorick; Jordyn A. Mitchell; Ruth H. Bledsoe; Michael L. Floren; Ross M. Wilkins (Journal of Orthopaedic Surgery and Research, 2020)
Abstract Background Despite improvements in treatment options and techniques, articular cartilage repair continues to be a challenge for orthopedic surgeons. This study provides data to support that the 2-year Cryopreserved, Thin, Laser-Etched Osteochondral Allograft (T-LE Allograft) embodies the necessary viable cells, protein signaling, and extracellular matrix (ECM) scaffold found in fresh cartilage in order to facilitate a positive clinical outcome for cartilage defect replacement and repair. Methods Viability testing was performed by digestion of the graft, and cells were counted using a trypan blue assay. Growth factor and ECM protein content was quantified using biochemical assays. A fixation model was introduced to assess tissue outgrowth capability and cellular metabolic activity in vitro. Histological and immunofluorescence staining were employed to confirm tissue architecture, cellular outgrowth, and presence of ECM. The effects of the T-LE Allograft to signal bone marrow-derived mesenchymal stem cell (BM-MSC) migration and chondrogenic differentiation were evaluated using in vitro co-culture assays. Immunogenicity testing was completed using flow cytometry analysis of cells obtained from digested T-LE Allografts and fresh articular cartilage. Results Average viability of the T-LE Allograft post-thaw was found to be 94.97 ± 3.38%, compared to 98.83 ± 0.43% for fresh articular cartilage. Explant studies from the in vitro fixation model confirmed the long-term viability and proliferative capacity of these chondrocytes. Growth factor and ECM proteins were quantified for the T-LE Allograft revealing similar profiles to fresh articular cartilage. Cellular signaling of the T-LE Allograft and fresh articular cartilage both exhibited similar outcomes in co-culture for migration and differentiation of BM-MSCs. Flow cytometry testing confirmed the T-LE Allograft is immune-privileged as it is negative for immunogenic markers and positive for chondrogenic markers. Conclusions Using our novel, proprietary cryopreservation method, the T-LE Allograft, retains excellent cellular viability, with native-like growth factor and ECM composition of healthy cartilage after 2 years of storage at − 80 °C. The successful cryopreservation of the T-LE Allograft alleviates the limited availably of conventionally used fresh osteochondral allograft (OCA), by providing a readily available and simple to use allograft solution. The results presented in this paper supports clinical data that the T-LE Allograft can be a successful option for repairing chondral defects.